2016
DOI: 10.17795/mejrh-34037
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Fatigue, Disability, and Mobility and the Quality of Life in Patients with Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) is a chronic disease which is caused by demyelination in the central nervous system (CNS) in young adults. This disease affects independence and the ability to participate in family and community activities, thus affecting the quality of life. Objectives: This cross-sectional study was designed to investigate the associations between fatigue, disability, and mobility and the quality of life in patients with MS in the city of Semnan, Iran. Patients and Methods: Sixty-six MS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Higher EDSS was associated with poorer MusiQoL index; it also predicted worse 'activities of daily living' and 'coping'; similar to previous findings. 8,31,32,35,36,[60][61][62] Developing interventions to improve the QoL coping dimension in MS patients with higher EDSS is necessary, with particular relevance to women in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher EDSS was associated with poorer MusiQoL index; it also predicted worse 'activities of daily living' and 'coping'; similar to previous findings. 8,31,32,35,36,[60][61][62] Developing interventions to improve the QoL coping dimension in MS patients with higher EDSS is necessary, with particular relevance to women in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied domains related to QoL in MS previously studied in the MENA region were depression, 9,10,30-33 fatigue, 10,32,34,35 and Figure 1. Literature search flow chart.…”
Section: Literature Search Findingsmentioning
confidence: 96%
See 2 more Smart Citations
“…It can be concluded that patients with advanced age or those who are diagnosed a relatively long time ago, due to limited physical and mental abilities, may need more occupational therapy to improve their QoL. In contrast, as stated by Kamran et al, age does not always affect PHC and MHC [31], and it had been argued that older patients had just lower MHC scores than younger ones [32].…”
Section: Discussionmentioning
confidence: 99%